AGE AND GENDER DISTRIBUTION OF ODONTOGENIC CYSTS - A RETROSPECTIVE STUDY (Journal of Pharmaceutical Negative Results, 2022)
Odontogenic cysts are considered relatively rare cystic lesions which affect the maxillofacial region. They can be classified based on their origin as Inflammatory cysts or Developmental cysts. These cysts are characterised by slow growth and a tendency to expand. In spite of presenting with benign biological behaviour, they can reach considerable size if not diagnosed or treated appropriately. There is however limited literature regarding the age and gender distribution of odontogenic cysts in the geographical location where the study is undertaken. The aim of the present study is to evaluate the age and gender distribution along with the frequency and site of occurrence of Odontogenic cysts (OC). It is a University/Hospital based study. 33 patients diagnosed with Odontogenic cystic lesions were included in the study. The age, gender, type of odontogenic cyst and site affected were evaluated. The data collected was imported to IBM SPSS Version 20 for analysis. It was observed that radicular cyst was the most frequently occurring cyst(54%) and greater predilection for OCs was seen in males than in females. Higher frequency of occurrence of OCs in the upper arch (53%) was observed with significant association between cyst type and site (p<0.05). Most common age of occurrence was in the 2nd-3rd decade of life. Within the limits of the study, it was observed that a greater prevalence of radicular cysts was seen, in the 2nd-3rd decade of life, with higher frequency in the upper arch and in male population.